Development and validation of a disease-specific quality of life questionnaire for patients with peripheral artery disease (QOLPAD) - Ebru-Berrin Arman; Matthias Augustin; Nicole Mohr; Sebastian E. Debus; Peter Breuer; Christine Blome (SpringerOpen, 2022)
Abstract Background The aim of this study was to develop and validate a short and feasible questionnaire to measure health-related quality of life (HRQoL) in patients with peripheral artery disease (PAD). The content of the new instrument is intended to correspond with the simultaneously developed instrument Patient Benefit Index for PAD (PBI-PAD), which evaluates treatment goals and benefits in this patient group. Methods Fifty patients stated their disease burden on free-text questionnaires, which was used by an interdisciplinary expert panel to develop 12 items for the new instrument, named Quality of Life questionnaire for patients with peripheral artery disease (QOLPAD). The validity of the instrument was tested in patients from Germany with PAD stages I to IV who completed the QOLPAD, EuroQol questionnaire (EQ-5D-3L; EuroQol visual analogue scale (EQ VAS)), and Vascular Quality of Life questionnaire (VascuQoL) before (baseline) and three months after (follow-up) treatment. Results One hundred and three patients were included at baseline (mean age: 68.6 years; 68% male), among whom, 57 provided data at follow-up. Most patients (86.4%) rated the completion of QOLPAD as being easy. Internal consistency was satisfactory, with a Cronbach's alpha of 0.74 (baseline) and 0.84 (follow-up). Convergent validity was indicated by significant correlations with the EQ-5D-3L (baseline: − 0.62; follow-up: − 0.81), EQ VAS (baseline: − 0.44, follow-up: − 0.79), VascuQoL global score (baseline: − 0.77; follow-up: − 0.87), global rating of impairment (baseline: 0.64; follow-up: 0.71), and PAD stage (baseline: 0.40; follow-up: 0.67). Sensitivity to change was confirmed by significant correlations of change in the QOLPAD with changes in convergent criteria; however, the high number of dropouts limits the generalizability of this finding. Conclusion This study provided evidence that the QOLPAD is internally consistent and valid in patients receiving treatment for PAD in Germany.